2011
DOI: 10.1097/smj.0b013e3182241da1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Osteoporosis Among Men in the Primary Care Setting

Abstract: A significant percentage of men are unaware of the complications and risk factors for osteoporosis. Receiving educational information about osteoporosis from a physician should be considered at an early stage, especially for those patients with modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…The respondents in this study had limited knowledge of osteoporosis (38.5% correct in the OKAT), a result comparable with the studies in other places like the United States (Gaines et al, 2011; Shawa, Favela, & Diaz, 2011) or Hong Kong (Lee & Lai, 2006). Unlike other studies, this study reported better knowledge in the younger respondents, and men in the younger age-groups had similar knowledge as women.…”
Section: Discussionsupporting
confidence: 86%
“…The respondents in this study had limited knowledge of osteoporosis (38.5% correct in the OKAT), a result comparable with the studies in other places like the United States (Gaines et al, 2011; Shawa, Favela, & Diaz, 2011) or Hong Kong (Lee & Lai, 2006). Unlike other studies, this study reported better knowledge in the younger respondents, and men in the younger age-groups had similar knowledge as women.…”
Section: Discussionsupporting
confidence: 86%
“…Fewer good-quality trials of osteoporosis treatment have been conducted in men compared to women, and trials focused on male participants are less likely to have a preventive purpose [2,3]. Male patients and primary care physicians appear to have low awareness of male osteoporosis [4], with typically low rates of bone mineral density (BMD) testing [5]. In the US, Medicare insurance only covers BMD testing in men for a limited number of disease conditions, not including routine screening [6].…”
Section: Introductionmentioning
confidence: 99%
“…Men have received very little research attention even though 20–25 % of osteoporosis fractures occur in men ( 21 ) . The few studies in men suggest an overall deficit in knowledge of osteoporosis and its risk factors ( 22 , 23 ) . Therefore, the aims of the present study were to assess knowledge of osteoporosis and its risk factors and to explore the association between various sociodemographic factors and knowledge of osteoporosis in Indian adults above 40 years of age.…”
mentioning
confidence: 99%